Samson og Herakles og forholdet natur - kultur - Carstens, Pernille (Religionsvidenskabeligt Tidsskrift, 1995)
The biblical Samson-narrative told in Judges 13-16 could be called a hero-narrative. The Samson-figure acting like a hero is know from the myths and legends of the neighbouring cultures. The article especially pays attention to the Greek Heracles tradition as a parallel to the Samson-story. The approach is based upon the idea that, from the second millennium B.C., eastern mediterranean cultures make up a "koine-culture". There is a kind of "family likeness" between these different hero-narratives forming a complex network. The folklore study is a new and fertile approach to the hero tradition. The article primarily stressed Susan Niditch's and D. Bynum's works. One of the most important topics in the hero tradition is the contrast between nature and culture. One dimension that brings this dichotomy to the fore is the hero's relation to women by whom he is subdued. She forces/seduces him to become more "culture" than "nature". She is taming the wild man by "womanization". Finally the article gives heed to the death of Samson and Heracles, showing that even though culturalized the death is triggered by nature.